What do young adolescents think about taking part in longitudinal self-harm research?: findings from a school-based study - Lockwood, Joanna; Townsend, Ellen; Royes, Leonie; Daley, David; Sayal, Kapil (BioMed Central, 2018)
Background: Research about self-harm in adolescence is important given the high incidence in youth, and strong links to suicide and other poor outcomes. Clarifying the impact of involvement in school based self-harm studies on young adolescents is an ethical priority given heightened risk at this developmental stage. Methods: Here, 594 school-based students aged mainly 13-14 years completed a survey on self-harm at baseline and again 12-weeks later. Change in mood following completion of each survey, ratings and thoughts about participation, and responses to a mood-mitigation activity were analysed using a multi-method approach. Results: Baseline participation had no overall impact on mood. However, boys and girls reacted differently to the survey depending on self-harm status. Having a history of self-harm had a negative impact on mood for girls, but a positive impact on mood for boys. In addition, participants rated the survey in mainly positive/neutral terms, and cited benefits including personal insight and altruism. At follow-up, there was a negative impact on mood following participation, but no significant effect of gender or self-harm status. Ratings at follow-up were mainly positive/neutral. Those who had self-harmed reported more positive and fewer negative ratings than at baseline: the opposite pattern of response was found for those who had not self-harmed. Mood mitigation activities were endorsed. Conclusions: Self-harm research with youth is feasible in school settings. Most young people are happy to take part and cite important benefits. However, the impact of participation in research appears to vary according to gender, self-harm risk and method/time of assessment. The impact of repeated assessment requires clarification. Simple mood-elevation techniques may usefully help to mitigate distress.